The Impact of Obesity on Breast Cancer Development in Women: A Study from Kirkuk Governorate, Iraq: Obesity and breast cancer - Najm, Hamzah mahmood; Hussain, Omar Abboud; Kamal, Maryam Ahmed (Iraqi Journal of Cancer and Medical Genetics, 2025)
Objective: Breast cancer (BC) is a malignant tumor arising in breast tissue due to abnormal cell growth and has the ability to spread to other body parts. It is the second most prevalent cancer, and its incidence rate among women has significantly increased, prompting research into contributing factors. Obesity is recognized as a critical factor linked to the development and dissemination of this disease. This research aims to understand the potential impact of obesity on BC development in women.Methods: A statistical analysis was conducted with 130 women diagnosed with breast cancer to evaluate the relationship between obesity levels and the development and dissemination of BC among obese women in Iraq (Kirkuk governorate). Data were collected via a specifically designed questionnaire, which classified obesity levels as moderate or high. SPSS Statistics software was used for data processing and analysis. Relationships and differences among the variables were assessed via the chi-square test, t test, and standard deviation.Results: The analyses revealed a significant increase in obesity prevalence among women with BC. These findings indicate that obese women are at increased risk of developing BC, highlighting obesity as a potential risk factor for this disease.Conclusion: The findings of this study underscore that obesity is a considerable risk factor linked to an increased probability of BC development in women. Statistical analysis confirmed that obesity rates were significantly higher among women diagnosed with BC. These findings support the notion that excess weight may significantly contribute to the onset and progression of the disease. Evidence suggests that obesity influences various biological processes contributing to cancer, including chronic inflammation, hormonal changes, and elevated insulin levels. Emphasizing obesity as a risk factor for BC is crucial for developing effective prevention and treatment strategies.